2006
DOI: 10.1021/ac058044j
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Thermally Stable Recombinant Anti-Caffeine Heavy-Chain Antibody Fragment

Abstract: We have isolated and characterized a caffeine-specific, heavy-chain-only antibody fragment (V(HH)) from llama that is capable of being utilized to analyze caffeine in hot and cold beverages. Camelid species (llama and camel) were selected for immunization because of their potential to make heat-stable, heavy-chain-only antibodies. Llamas and camels were immunized with caffeine covalently linked to keyhole limpet hemocyanin, and recombinant antibody techniques were used to create phage displayed libraries of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(110 citation statements)
references
References 18 publications
3
104
0
1
Order By: Relevance
“…Camelid VHH is famous for its high thermodynamic stability (25)(26)(27). Unique applications are proposed to utilize this high stability of VHH, such as detection of caffeine in hot beverages (28) and prevention of dandruff by VHH mixed with shampoo containing a high concentration of surfactant (29). Stabilization by the engineered disulfide bond reinforces the utility of VHHs.…”
Section: Discussionmentioning
confidence: 99%
“…Camelid VHH is famous for its high thermodynamic stability (25)(26)(27). Unique applications are proposed to utilize this high stability of VHH, such as detection of caffeine in hot beverages (28) and prevention of dandruff by VHH mixed with shampoo containing a high concentration of surfactant (29). Stabilization by the engineered disulfide bond reinforces the utility of VHHs.…”
Section: Discussionmentioning
confidence: 99%
“…The binding site formed from a single domain that is small, highly stable, and able to refold properly after denaturation, makes the HcAb variable domain a valuable source of alternative recombinant binding ligand for many applications. [24][25][26] The aim of this research was to evaluate the diphtheria toxin-binding capability of antibodies obtained from the immunized camel. Earlier work had shown that camel HcAb was active towards pathogens, and the ability to create single-domain antibodies from immunized libraries attests to their antigen recognition capability.…”
Section: Discussionmentioning
confidence: 99%
“…Several anticaffeine VHHs have been already generated for the quantification of caffeine in hot beverages. At 70°C, one of these VHHs could recognize caffeine and amazingly recover its binding functionality after an incubation step at 90°C, 110 demonstrating the excellent thermostability of these nanobodies.…”
Section: Nanobodies For Agricultural Protection and Food Analysismentioning
confidence: 95%